STANDAR TIKTOK SEBAGAI REALITAS PERUBAHAN SOSIAL BUDAYA PADA MASYARAKAT MODERN - Dina Sudarmika; Sachrin Suci Helmina; Sila Nirmala (Prodi Ilmu Komunikasi Universitas Putera Batam, 2025)
TikTok, as a social media platform that offers entertainment, information, and educational content, has become an integral part of modern digital life. It significantly influences cultural trends, lifestyles, and consumption patterns, serving as a reflection of ongoing social and cultural transformations. One notable phenomenon is the emergence of the so-called “TikTok standard” — particularly in terms of lifestyle and beauty norms — which shapes public perceptions and behaviors. This study aims to analyze how these TikTok standards contribute to social and cultural changes within society. Employing a qualitative approach with a descriptive analysis method, the research presents detailed and clear information to enhance understanding of the data. The findings reveal that TikTok standards have significant implications for social change, driven by globalization, information technology, and consumer culture. These standards influence lifestyle shifts and redefine beauty ideals in modern society.